Using virtual microscopy for the development of sampling strategies in quantitative histology and design-based stereology - Kolinko, Yaroslav; Malečková, Anna; Kochová, Petra; Grajciarová, Martina; Blassová, Tereza; Kural, Tomáš; Trailin, Andriy; Červenková, Lenka; Havránková, Jiřina; Vištejnová, Lucie; Tonarová, Pavla; Moulisová, Vladimíra; et al. (Anatomia, histologia, embryologia, 2022)
Only a fraction of specimens under study are usually selected for quantification in histology. Multilevel sampling or tissue probes, slides and fields of view (FOVs) in the regions of interest (ROIs) are required. In general, all parts of the organs under study should be given the same probability to be taken into account; that is, the sampling should be unbiased on all levels. The objective of our study was to provide an overview of the use of virtual microscopy in the context of developing sampling strategies of FOVs for stereological quantification. We elaborated this idea on 18 examples from multiple fields of histology, including quantification of extracellular matrix and muscle tissue, quantification of organ and tumour microvessels and tumour-infiltrating lymphocytes, assessing osseointegration of bone implants, healing of intestine anastomoses and osteochondral defects, counting brain neurons, counting nuclei in vitro cell cultures and others. We provided practical implications for the most common situations, such as exhaustive sampling of ROIs, sampling ROIs of different sizes, sampling the same ROIs for multiple histological methods, sampling more ROIs with variable intensities or using various objectives, multistage sampling and virtual sampling. Recommendations were provided for pilot studies on systematic uniform random sampling of FOVs as a part of optimizing the efficiency of histological quantification to prevent over- or undersampling. We critically discussed the pros and cons of using virtual sections for sampling FOVs from whole scanned sections. Our review demonstrated that whole slide scans of histological sections facilitate the design of sampling strategies for quantitative histology.
Keywords: sampling; mikroskopie; Animals; Bone and Bones; mozek; Brain; kosti a kostní tkáň; histologické techniky; histological slides; Histological Techniques; Microscopy; veterinary histology; quantitative microscopy; zvířata; study design; stereology